17β-Estradiol inhibits TNF-α-induced proliferation and migration of vascular smooth muscle cells via suppression of TRAIL. (2nd July 2016) - Li, Hengchang; Cheng, Yang; Simoncini, Tommaso; Xu, Shiyuan
Abstract: Atherosclerosis is an inflammatory disease and involves migration of vascular smooth muscle cells (VSMCs). Estrogen inhibits VSMCs migration, while the underlying mechanism remains to be revealed. Recent years, there is emerging evidence showing that TNF-related apoptosis-inducing ligand (TRAIL) increases proliferation and migration of VSMCs. In this study, we investigated the regulatory effect of estrogen on TRAIL expression in VSMCs. TNF-α greatly enhanced TRAIL protein expression and stimulated VSMCs proliferation and migration. This effect was partially inhibited by the addition of TRAIL neutralizing antibody, suggesting that TRAIL is important in TNF-α-induced migration. 17β-estradiol (E2) inhibited TRAIL expression under TNF-α stimulation in a time- and concentration-dependent manner. This effect was was mimicked by ERα agonist 4′, 4″, 4‴-(4-propyl-[1H]-pyrazole-1, 3, 5-triyl) trisphenol (PPT), but not ERβ agonist 2, 3-bis-(4-hydroxyphenyl)-propionitrile (DPN), indicating that ERα is involved in this action. TNF-α led to nuclear factor kappa B (NF-κB) p65 phosphorylation and the inhibitor pyrrolidine dithiocarbama (PDTC) inhibited TRAIL expression, suggesting that NF-κB signaling is crucial for TARIL production. E2 suppressed p65 phosphorylation in VSMCs and the overexpression of p65 subunit reversed the inhibitory effect of E2 on TRAIL expression and cell proliferation and migration. Taken together, our results indicate that E2 inhibits VSMCs proliferation and migration by downregulation of TRAIL expression via suppression of NF-κB pathway.